2016
DOI: 10.5114/ada.2016.63880
|View full text |Cite
|
Sign up to set email alerts
|

The possible role of diet in the pathogenesis of adult female acne

Abstract: Acne in adults is a chronic, increasingly common disease, especially among women. It differs in pathogenesis and clinical presentation from adolescent acne. Acne in adults is associated with Western diet, defined as high consumption of milk, high glycemic load and high calorie intake. Metabolic signals of this diet result in a significant increase in insulin/insulin growth factor 1 serum level and consequently in the molecular interplay of mammalian target of rapamycin complex 1 kinase (mTORC1)/forkhead box pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 51 publications
1
17
0
2
Order By: Relevance
“…While, serum TC, HDL, and LDL showed no significant difference between both studied groups. Concerning IR level in postadolescent acne patients, our result was in accordance with two studies 17,18 and opposed by only one study. 19 This difference is due to the fact that in the latter study, the studied groups were on low glycemic diet for at least 2 weeks prior to HOAM-IR test, which was not the case in the current study.…”
Section: Discussionsupporting
confidence: 91%
“…While, serum TC, HDL, and LDL showed no significant difference between both studied groups. Concerning IR level in postadolescent acne patients, our result was in accordance with two studies 17,18 and opposed by only one study. 19 This difference is due to the fact that in the latter study, the studied groups were on low glycemic diet for at least 2 weeks prior to HOAM-IR test, which was not the case in the current study.…”
Section: Discussionsupporting
confidence: 91%
“…It is a multifactorial disease, originating in the pilosebaceous unit. Although much research has been conducted on acne, the aetiology of acne vulgaris remains poorly understood [ 1 4 ]. The current view is that acne is related to factors such as androgen, hyperseborrhea, hyperkeratosis of the pilosebaceous ducts, follicular orifice blockage, and proliferation of bacteria, such as Propionibacterium acnes , and Staphylococcus epidermidis [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent studies, apart from the consumption frequency of foodstuffs with high glycemic index values, the consumption frequency of certain foodstuffs with low glycemic index value was also found to be high in AV patients. 16,34,35 In this regard, we found that acne is triggered by foodstuff such as feta, cola, cheese, and peanut in which insulin index value was higher than glycemic index value. This result may suggest that insulin index may be used as another marker for AV-triggering foodstuffs.…”
Section: Case Control a Total Of 3826 Acne Vulgaris Patients And 759 mentioning
confidence: 85%